Rifle Shooting for Athletes With Vision Impairment: Does One Class Fit All? - Allen, Peter M.; Latham, Keziah; Ravensbergen, Rianne H. J. C.; Myint, Joy; Mann, David L. (Frontiers in Psychology, 2019)
Revised evidence-based entry criteria for visually-impaired shooting suggest that athletes with impaired contrast sensitivity (CS) and visual acuity (VA) worse than 0.6logMAR should be eligible for inclusion in the sport, rather than 1.0logMAR as previous. Is more than one class necessary for the sport with the revised minimum entry criterion? Twenty-five elite VI shooting athletes took part in the study. Two measures of visual function were assessed under standardised conditions: VA (using an ETDRS logMAR letter chart, and / or a BRVT chart) and CS (using both a Pelli-Robson chart and a Mars number chart). Shooting performance, in both prone and standing events, was measured during an international VI shooting competition. Fourteen of the 25 athletes had measurable VA, including 6 with VA better than 1.0logMAR. For CS, 8 athletes had measurable function with the Pelli-Robson chart and 13 with the Mars chart. The remaining athletes had function not numerically measurable by the charts and were considered to have no residual vision. There was no indication that shooting performance varied with visual function, and individuals with residual vision had no advantage over those without vision for either prone or standing shooting. The modifications made to the sport of VI shooting would appear to successfully render the sport of VI shooting equitable for all athletes with VA of less than or equal to 0.6 logMAR. Only one class is necessary for athletes once deemed as eligible to compete in VI shooting. An improved method of measuring CS in athletes with profound VI would be advantageous.